Lattice‐based revocable attribute‐based encryption with decryption key exposure resistance - Xingting Dong; Yupu Hu; Baocang Wang; Momeng Liu; Wen Gao (IET Information Security)
Abstract Attribute‐based encryption (ABE) is a promising management method that enables fine‐grained access control in large‐scale systems. Revocable ABE (RABE) can support a key revocation mechanism in an ABE system. With the advent of the Internet of Things, users may need to delegate their decryption capacity to other devices, which requires that RABE meet a necessary feature called decryption key exposure resistance (DKER). Although many constructions about RABE from bilinear maps have been proposed, the situation of lattice‐based constructions with DKER is less satisfactory. In order to narrow this gap, this paper propose the first lattice‐based RABE with DKER. First, a formal description of RABE with DKER and the corresponding security models is proposed. Subsequently, a lattice‐based RABE scheme without DKER is constructed and it is proved to be selective indistinguishability under chosen‐plaintext attack (IND‐CPA) security based on Learning with Errors (LWE). To achieve DKER, this paper construct a RABE scheme by using the RABE scheme without DKER and a key extension mechanism as its building blocks. Finally, this paper show that this scheme is selective IND‐CPA security, with the DKER based on LWE.